2022
DOI: 10.1177/17479541221085236
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the criterion validity and reliability of technical and tactical field-based tests in soccer

Abstract: Background Field-based tests are important since they can guarantee ecological validity. Although most such tests are designed to assess physical fitness, tactical and technical dimensions are also determinants in a full battery of tests. Objectives This systematic review aimed to (a) summarize the criterion validity and reliability of technical and tactical field-based tests applied in soccer and (b) list valid and reliable technical and tactical field-based tests. Methods A systematic review of EBSCO, PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…During the game teaching process, it is possible to identify a tendency to direct it to the goal and forget defensive phase content, such as contention, coverage, balance, and concentration [ 56 ]. The process of sport initiation in collective games should provide the practitioner tactical procedural knowledge by activities related to the formal game [ 10 , 12 , 39 ]. That may help players to learn the offensive and defensive dynamics and processes of the sport [ 18 , 19 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the game teaching process, it is possible to identify a tendency to direct it to the goal and forget defensive phase content, such as contention, coverage, balance, and concentration [ 56 ]. The process of sport initiation in collective games should provide the practitioner tactical procedural knowledge by activities related to the formal game [ 10 , 12 , 39 ]. That may help players to learn the offensive and defensive dynamics and processes of the sport [ 18 , 19 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is fundamental for football players to develop tactical knowledge, which is mediated by decision making and motor efficiency [ 9 , 10 ]. The tactical knowledge seems to be influenced by field position, though it can also be considered that each field position leads to specialized decision making and motor efficiency across the developmental stages [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…One way to improve the ecological validity of an assessment is to conduct it in a setting that is as similar as possible to the real-world setting in which the players perform. For example, if you are interested in assessing the technical skill of adolescent soccer players, you could conduct the assessment during a soccer practice or match rather than in a laboratory setting [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the sports where the production has been most prolific is football. Thus, in the systematic review by Clemente et al [ 13 ], 21 studies were identified, of which 8 focused on tactical tests (e.g., FUT-SAT), 10 on technical tests (e.g., Loughborough Soccer Passing Test) and 3 on tests concurrent with physical aspects (e.g., MT5M). In other sports (e.g., basketball) there is an amalgam of instruments with different purposes, such as the influence of contextual variables on tactical thinking [ 14 ], the player discrimination by position according to physical–technical execution patterns [ 15 ] or the relevance of physiological parameters [ 16 ].…”
Section: Introductionmentioning
confidence: 99%